Reformasi kebijakan kesehatan dan sistem asuransi: A systematic literature review - Karimin Karimin; Masriawati Masriawati; Sartini Risky; La Ode Liaumin Azim (Holistik Jurnal Kesehatan, 2026)
Background: Health policy and insurance system reforms are crucial instruments for achieving universal health coverage (UHC) and ensuring equitable access to medical services. With aging populations and rising healthcare costs across various nations, restructuring insurance frameworks has become a global priority. Purpose: To analyze the trajectory of development, policy implementation, financing, and insurance system reforms within healthcare services. Method: This study is a systematic literature review utilizing relevant and objective academic databases. Searches were conducted using keywords related to policy implementation and healthcare financing across Scopus, PubMed, and ScienceDirect. The identification phase yielded 52 articles, which were subsequently examined using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were synthesized and presented thematically, grouping relevant findings according to established key themes: enhancing administrative efficiency, policy reform, and the reform of primary healthcare systems within insurance models and financing structures. Following systematic identification and review, 13 articles were deemed suitable for inclusion in the final synthesis. Results: Three key pillars of national insurance system reform were identified as essential for achieving universal health coverage (UHC) and bolstering public health resilience: policy reform, support for fiscal sustainability, and administrative reform driven by digital integration. Conclusion: Health insurance reform is an ongoing process that balances social equity with fiscal realities. The most successful reforms are grounded in three main pillars: fiscal innovation, technology adoption, and legislative support. To achieve sustainable universal health coverage (UHC), policymakers must prioritize data interoperability and human resource training. Suggestion: Future research should examine the long-term impact of AI-based premium setting on patient trust and equity within the insurance system.   Keywords: Health Service Administration; Health Service Policy; Insurance Reform; Universal Health Coverage.